Fuzzy metric for evaluating performance in the process management - Kraenau Espinal, Erwin (2016)
Designing a performance metric by the fuzzy logic, the purpose of which is incorporated more aspects of the management processes of any organization including those subjective. To show how this metric was applied prior to a billing process of a company of herbicides, where this metric was constructed by traditional indicators of efficiency and effectiveness, producing fuzzy performance measures. The results show that this fuzzy measure performance is stable and valid as it is built on classical performance indicators already familiar with the properties they own. These metrics diff se somehow standardize the processes of the organization. The construction of the software and the results obtained from the fuzzy logic module of MATLAB version 7.0 (fuzzy toolbox).